Total lumbar disc replacement from posterolateral approach - Slinko, E. I.; Al-Qashqish, Iyad I.; Kvasnitsky, O. M. (Ukrainian Neurosurgical Journal, 2008)
There were 5 operated patients whom posterolateral approach for total lumbar disc replacement was used. In all patients single-level disk hernia was diagnosed. The follow-up range was 6–12 months. Patients reported their pain on the Visual Analogue Scale and completed the Oswestry Disability Index questionnaire. According to roentgen data disc height and motion ranges were assed both before and after surgery. All patients noticed reduced low back pain and significantly improved leg pain. Visual analogue pain scale score decreased from 87,1±3,1 before surgery to 22,3±6,1 — 6 months after it. The Oswestry Disability Index decreased from 72,3±9,1 before operation to 26,2±14,4 — 6 months after intervention. In average preoperative height of the affected discs was 7 mm, whereas after intervention it increased to 12,5 mm. Motion at the affected disc level increased from 5° before operation to 11° after it. The adjacent-level disc heights did not significantly change. There were no cases of prosthesis subsidence, loosening, dislocation or failure of the device’s metallic or polyethylene components. The development of posterolateral approach and modified implants may allow apply total disc replacement technique at patients with sciatica due to lumbar disc hernia and has definite additional advantages over anterior surgery in lumbar disk hernia patients.